Sexual uses of alcohol and drugs and the associated health risks: A cross sectional study of young people in nine European cities - Mendes Fernando; Rodriguez José A; Ramon Anna; Juan Montse; Calafat Amador; Hughes Karen; Bellis Mark A; Schnitzer Susanne; Phillips-Howard Penny (BMC, 2008)
Abstract Background Young people in European countries are experiencing high levels of alcohol and drug use and escalating levels of sexually transmitted infections. Individually these represent major public health priorities. Understanding of the association between sex and substance use, and specifically the strategic roles for which young people utilise substances to facilitate sexual activity, remains limited. Methods Respondent driven sampling methodology was used in nine European cities to survey 1,341 16-35 year olds representing youth and younger adults who routinely engage in nightlife. Participants self-completed questionnaires, designed to gather demographic, social, and behavioural data on historic and current substance use and sexual behaviour. Results Respondents reported strategic use of specific substances for different sexual purposes. Substances differed significantly in the purposes for which each was deployed (e.g. 28.6% of alcohol users use it to facilitate sexual encounters; 26.2% of cocaine users use it to prolong sex) with user demographics also relating to levels of sexual use (e.g. higher levels of: ecstasy use by males to prolong sex; cocaine use by single individuals to enhance sensation and arousal). Associations between substance use and sex started at a young age, with alcohol, cannabis, cocaine or ecstasy use before age 16 all being associated with having had sex before the age of 16 (odds ratios, 3.47, 4.19, 5.73, 9.35 respectively). However, sexes differed and substance use under 16 years was associated with a proportionately greater increase in early sex amongst girls. Respondents' current drug use was associated with having multiple sexual partners. Thus, for instance, regular cocaine users (c.f. never users) were over five times more likely to have had five or more sexual partners in the last 12 months or have paid for sex. Conclusion An epidemic of recreational drug use and binge drinking exposes millions of young Europeans to routine consumption of substances which alter their sexual decisions and increase their chances of unsafe and regretted sex. For many, substance use has become an integral part of their strategic approach to sex, locking them into continued use. Tackling substances with both physiological and psychological links to sex requires approaching substance use and sexual behaviour in the same way that individuals experience them; as part of the same social process.